Applying AIM-9X on MiG-29 – Initial Analysis of MiG-29 Weapon System Modernizations - Norbert GRZESIK (Wojskowa Akademia Techniczna, 2012)
Author, in this article, describes technical realizability of assembly AIM-9X missile on MiG-29, gives also in the introduction information about aircraft modernizations necessity. Second and third part of the article consist of technical, physical and operating data of AIM-9X air to air missile, LAU-129A/A missile launcher and missile launcher adapter. Fourth part contains mechanical and electric adaptations. Fifth part includes description of weapon control system and blocks locations. Conclusions end the publication. This article is integral part of author’s scientific research and cooperation with Armament Market Analyzing Office of Ministry of Defense
Keywords: Modernizacja uzbrojenia samolotu MIG-29